The Prevalence of Alimentary Tract Worms in Domestic Cats and Stray Cats at Campus Area of Semarang State University, Central Java - Farantika, Rafita; Susanti, R. (Jurnal Veteriner, 2019)
The aims of this study were to identify and measure the prevalence of alimentary tract worm in stray and domestic cats in the campus area of Semarang State University (Universitas Negeri Semarang/Unnes). As many as 30 cat feces samples: 10 stray cats samples (SC), 10 limited range domestic pet cats (LDC), and 10 indoor domestic pet cats (IDC) were used in this study. Examination of the feces samples was done by using the flotation method to identify the eggs of worms. Based on feces examination, eggs of four worms species i.e. Ancylostoma caninum, Clonorchis sinensis, Dipylidium caninum and Toxocara cati were found. Based the prevalence of worm eggs: A. caninum was found infected 4 out of 30 samples (13.3%), C. sinensis was found infected 2 out of 30 samples (6.6%), D. caninum was found infected 2 out of 30 samples (6.6%), and T. cati was found infected 10 out of 30 samples (33.3%).